E-Banking as a Financial Supply Chain System: Can e-TAM improve Trust and the Rate of Adoption? - Maruf Gbadebo Salimon; Sany Mohd Mokhtar Sanuri; Maha Mohammed Yusr (International Journal of Supply Chain Management, 2020)
Electronic banking as a financial supply chain system has gone a long way to revolutionize banking services as contemporary customers of banking organizations have largely moved from brick and mortal banking to digital platform. However, trust remains an important underlying factor that makes users from developing countries to be wary of the way they adopt this novel technology banking system. The significant objective of this study therefore centres on how to improve trust using extended technology acceptance model (e-TAM) by incorporating perceived security and e-trust with perceived usefulness and perceived ease of use to predict adoption of e-banking. Previous studies have paid meagre attention to this area, especially in a developing context.  The data of the study were collected from 266 customers while the responses obtained were analysed using Partial Least Square Structural Equation Modelling. The findings show that perceived usefulness and perceived ease use predicted e-trust and e-banking adoption. Perceived security also predicted e-banking adoption but failed to predict e-trust. E-trust mediates the relationship between perceived usefulness, perceived ease of use and e-banking adoption. However similar mediating effect was not found between perceived security and e-banking adoption. The implications of the study were presented.